2004
DOI: 10.1149/1.1782634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti Incorporation in Ni on Silicidation Reaction and Structural/Electrical Properties of NiSi

Abstract: The effects of Ti incorporation in a Ni film on the silicidation reaction as well as the structural and electrical properties of NiSi have been investigated. Experimental results from this work showed that the reaction-inhibiting effect of an interfacial oxide layer could be effectively overcome by Ti incorporation. It was found that, in the presence of a thin interfacial oxide ͑1-2 nm͒, the onset of the silicidation reaction occurs at 300°C with a Ni͑5 atom % Ti͒ alloy while the thin interfacial oxide effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…This conclusion was similarly reported by R.T.P. Lee et al using Ni and Ti alloy targets [11]. Also as our results showed, the sheet resistance was larger with the samples having a larger proportion of Ti in the Ni layer.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This conclusion was similarly reported by R.T.P. Lee et al using Ni and Ti alloy targets [11]. Also as our results showed, the sheet resistance was larger with the samples having a larger proportion of Ti in the Ni layer.…”
Section: Resultssupporting
confidence: 92%
“…R.T.P. Lee et al considered that this was due to the increase of the thickness of the Ti-related layer with increasing proportion of Ti [11]. And D. Deduytsche et al reported that a small amount of refractory can dissolve into the NiSi lattice or can be present at the grain boundaries, decreasing the NiSi grain size, and presented this result as another possible reason for the increase of sheet resistance [9].…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is similar to the formation of NiSi 2 by annealing a Ni(Ti)/oxide/Si film stack at 300 C, where the oxide layer acts as a diffusion barrier. 39 In addition, the thermodynamic driving force (negative DG total ) for the nucleation of NiSi 2 on Si at a low temperature can be provided by the following factors: (1) the low interfacial energies 39,40 DG i at the NiSi 2 /Si(100) and NiSi 2 /Si(111) interfaces as compared to that of NiSi/Si(100) interface, (2) the small lattice mismatch (0.4%) between NiSi 2 and Si, 39,41 and (3) the small volume change 42 of only 2% arising from the difference in thickness between NiSi 2 and Si (volume change for the difference in thickness between NiSi and Si is 10%). Furthermore, due to the fact that (111) planes of NiSi 2 are parallel to Si (111) and the nucleation of NiSi 2 is easiest on (111) Si planes, the NiSi 2 crystallites therefore take the form of a pyramidal shape.…”
Section: Discussion On the Formation Of Nickel Disilicde And Nickementioning
confidence: 99%
“…2 However, formation of Ni silicide has been found to be very sensitive to the presence of native oxide at the Ni/ Si interface. 3 Ti capping, 4 Ti interlayer, 5 or Ti alloying 6 has been reported to successfully tackle the problem of residual interfacial oxide. After metal deposition, silicide formation is usually carried out by subjecting the whole device wafer to an elevated temperature for a short duration using rapid thermal annealing ͑RTA͒ process.…”
Section: Introductionmentioning
confidence: 99%